Specialized Courts and the Reporting of Intimate Partner Violence: Evidence from Spain - Jorge Garcia-Hombrados; Marta Martínez Matute (Institute of Labor Economics (IZA), 2021)
This paper assesses the effect of the creation of specialized intimate partner violence (IPV) courts on the reporting and incidence of these crimes. To achieve this goal, we exploit the sequential roll-out of specialized IPV courts throughout Spain by applying a difference-in-differences strategy over a sample of treatment and matched control districts. We find that the opening of a specialized IPV court decreases time to disposition of IPV cases by 61% and increases the reporting of IPV in the judicial district by approximately 22%. However, we do not see any effect of the courts on the incidence of IPV homicides, neither on the reported number of aggravated IPV offenses, for which misreporting is arguably smaller. The latter results suggest that despite the positive effects on the reporting of less severe IPV offenses, the creation of these courts failed to reduce the incidence of the most severe IPV offenses within the time period studied.
Keywords: J12; J16; K14; K38; 330; intimate partner violence; reporting of intimate partner violence; specialized intimate-partner violence courts